Advancing a Conceptual and Empirical Model of School Climate for School Staff in California. (2nd April 2020) - Capp, Gordon; Astor, Ron Avi; Gilreath, Tamika D
ABSTRACT: School climate is increasingly intertwined with efforts to create safe schools and improve social-emotional learning and academic outcomes. While current definitions of school climate implicate the decisions and actions of school staff members, the majority of school climate research focuses on the perspectives of students. This study presents an adapted model of school climate that focuses on the experiences of school staff members, and is one of the first empirical studies to explore a statewide data set of responses from staff members in California public schools. Results suggest that there are meaningful differences in the experiences of school climate for different staff members and that these differences should guide the assessments of school climate and changes to policies and procedures that may influence climate.